Analysis Of Box And Bored Pile Segment Planning In Tunnel Using Jacking Box Tunnel Method - Sajiwo Siti Haryanto; Maulidya Nur Sadya; Muhrozi; Undayani Cita Sari (Jurnal Ilmiah Dinamika Rekayasa, 2025)
Jacking box tunnel is a tunnel construction method which can be a solution when there are other buildings adjacent to the tunnel construction area. Jacking box tunnel is also a solution when the use of open excavation methods is not possible. The use of Culvert Box Segments inserted into the ground can minimize the impact on surrounding buildings so that soil stability can be maintained. PT Jaya Real Property provides pedestrian tunnel access to connect Jurang Mangu Station with BXC Mall. This tunnel has a total planned length of 161.4 meters, consisting of a total of 4 Culvert Box Segments. In the Culvert Box Segment 3 area, it intersects with the existing Jakarta-Serpong toll road abutment, therefore in order not to interfere with the existing abutment, the Jacking Box Tunnel construction method is used. In this study, a design analysis was carried out on a tunnel using this construction method. The results show that with the planning of Culvert Box Segment 3 along 41.7 meters, the implementation of the Jacking Box Tunnel requires a work area as deep as 7.6 m from the original ground surface. In this study, there are 3 groups of bored piles used to hold the soil for working area and supporting the implementation of the jacking process based on the existing load conditions. Bored pile 1 and Bored pile 3 are planned to use a diameter of 600 mm with 18 - D25 reinforcement, while Bored pile 2 uses a diameter of 800 mm and 18 - D25 reinforcement. Furthermore, the structure of the Culvert Box Segment is made of reinforced concrete with a reinforcement diameter of 22 mm and a jacking load requirement of 4901.9512 kN to push the Culvert Box Segment. One Culvert Box Segment requires 2 hydraulic jacks with a maximum capacity of one hydraulic jack of 400 tons.